The Effect of ESG Score on Default Risk With Ownership Concentration as Moderating Variables - Arellano Belva Radhiyya Putera; Cynthia Afriani Utama (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) score on corporate default risk by incorporating ownership concentration—measured through cash flow rights, control rights, and family ownership—as moderating variables. Grounded in agency theory, the study hypothesizes that ownership structure may strengthen or weaken the effectiveness of ESG implementation in mitigating financial risk. The research sample comprises 304 observations of publicly listed companies in Indonesia that had an ESG score between 2020 and 2023. Data analysis is conducted using fixed effect panel regression with clustered robust standard errors. The findings reveal that ESG score has a positive and significant effect on Z-score, indicating that companies with higher ESG performance tend to exhibit lower default risk. The moderating effect of cash flow rights weakens the ESG impact on default risk, while control rights significantly enhance it. Meanwhile, family ownership is found to be insignificant both as a main variable and as a moderator in the ESG–default risk relationship. These results emphasize the critical role of ownership structure in determining the effectiveness of ESG as a risk mitigation tool and highlight the need for adaptive governance and regulatory frameworks to support sustainability practices in corporations. This study contributes to the growing literature on ESG, ownership structure, and risk management in emerging markets.